Guidance Counsellor and Special Counsellor - Andrews, W. R. (Canadian Journal of Counselling and Psychotherapy, 2012)
Various solutions to the role problems of the Canadian counsellor suggest trimming the role either by lopping off psychological counselling on the one hand or vocational or other guidance activities on the other. If one role cannot in practice perform all the traditional counsellor activities, an added role may be needed. This paper advocates a model which would supplement the role of the guidance counsellor with the role of a special counsellor who would work with the troubled student.